Inhibitory effect of aloperine on transient outward potassium currents in rat cardiac myocytes - Dong, Xiao-Na; Li, Meng-Ting (Frontiers in Pharmacology, 2024)
Objective: Aloperine (ALO) is an effective quinolizidine alkaloid. Previous research has demonstrated its antiarrhythmic effect by inhibiting voltage-gated sodium currents in rat ventricular myocytes. This study explored its effect on transient outward potassium currents (Ito) in rat atrial myocytes to identify potential targets in the context of ion channel currents. Methods: The Ito characteristics in rat atrial myocytes were recorded using a whole-cell patch-clamp technique. Molecular docking was performed to validate ligand-protein binding interactions. Results: ALO at concentrations of 3 and 10 M significantly reduced Ito current densities. Gating kinetics analysis revealed ALO's ability to slow Ito activation, hasten inactivation, and prolong transition from inactive to resting state. Molecular docking revealed that ALO could stably bind to KCND2. Conclusion: ALO may inhibit Ito by slowing the activation process, accelerating inactivation, and delaying the recovery time after inactivation, potentially preventing acetylcholine-induced AF.